2022
DOI: 10.1039/d2ra01472f
|View full text |Cite
|
Sign up to set email alerts
|

A facile metal-free one-flask synthesis of multi-substituted furans via a BF3·Et2O mediated formal [4 + 1] reaction of 3-chloro-3-phenyldiazirines and α,β-alkenyl ketones

Abstract: A metal and oxidant free approach to multi-substituted furans from easily accessible 3-chloro-3-phenyldiazirines and α,β-alkenyl ketones in one flask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[119][120][121][122] Taking the advantage of this fact, Zhang et al in 2022 demonstrated a one-pot synthesis of multisubstituted furans 237 via inexpensive boron trifluoride catalyst in good to excellent yields. [123]…”
Section: Acid Catalyzed Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…[119][120][121][122] Taking the advantage of this fact, Zhang et al in 2022 demonstrated a one-pot synthesis of multisubstituted furans 237 via inexpensive boron trifluoride catalyst in good to excellent yields. [123]…”
Section: Acid Catalyzed Approachesmentioning
confidence: 99%
“…Taking the advantage of this fact, Zhang et al. in 2022 demonstrated a one‐pot synthesis of multisubstituted furans 237 via inexpensive boron trifluoride catalyst in good to excellent yields [123] . The products were obtained by three steps of cyclopropanation, Cloke‐Wilson rearrangement and elimination of HCl from α , β ‐alkenyl ketones 229 and 3‐chloro‐3‐phenyldiazirines 228 .…”
Section: Transition‐metal Free Synthesismentioning
confidence: 99%